Electrical Conductivity and Ion Transport Number Analysis of Polymer Nanocomposite Films - Sharma, Parul Kumar; Sharma, Anshul Kumar; Sadiq, M .; Sharma, A. L. (Asian Journal of Engineering and Applied Technology, 2016)
Solid state free standing polymer nanocomposite films have been used in numerous vitality related segments like: high energy density solid polymer batteries, PEM fuel cells, super capacitors, etc. Such applications require a desirable conductivity value of the order of 10-3 Scm-1 at room temperature. A free standing transparent film of solid state polymer electrolyte based on PEO+ LiPF6 with different compositions of nano sized filler (BaTiO3) in weight percent (x = 0, 1, 2, 5, 10, 15, 20 ) is synthesized by using standard solution cast technique. Surface morphology of the prepared polymer composition is examined by field emission scanning electron microscopy (FESEM). I-V characteristics of the prepared sample have been characterized for the stability of electrochemical potential window. The transport number analysis of prepared sample has been done to separate out the contribution due to ions and electrons in the electrical conductivity results. The transference number has been estimated and found of the order of 94%.